How Christianity changed the world - Schmidt, Alvin J. (Grand Rapdis, MI Zondervan, 2004)
Includes bibliographical references and index.
Originally published : Under the influence. Grand Rapdis, MI: Zondervan, c. 2001
Keywords: Christianity -- influence; Civilisation, Christian